Adsorption of Phenol from Aqueous Solution on to Activated Carbon. Effect of Solvent, Temperature and Particle Size - R. Leyva-Ramos; J.H. Soto Zuñiga; J. Mendoza Barron; R.M. Guerrero Coronado (Adsorption Science & Technology)
The effects of solvent, particle size and temperature on the adsorption isotherm for phenol on to activated carbon were investigated in this work. The first two effects were studied by determining the adsorption isotherm at 298 K in both aqueous and cyclohexane solutions, and using particle diameters of 0.338, 0.635, 0.940 and 1.494 mm. The last effect was analyzed by measuring the adsorption isotherm at temperatures of 283 K, 298 K and 313 K in both solvents, and using a particle diameter of 0.940 mm. It was found that in the aqueous solution the amount of phenol adsorbed is greater than that in the cyclohexane solution, which was attributed to the fact that phenol has a higher affinity for cyclohexane than for water. Furthermore, the results revealed that in aqueous solution the amount of phenol adsorbed increased when the particle size decreased and was slightly reduced by an increase in the temperature; however, in cyclohexane solution, the amount of phenol adsorbed was independent of particle size and considerably reduced by increasing temperature.